Asimetri Informasi, Corporate Social Responsibility, dan Intellectual Capital terhadap Nilai Perusahaan - Tjahja, Steven Adrian; Lindrawati, Lindrawati (https://jurnal.binamandiri.ac.id/, 2024)
The company aims to increase profits every year to show good company performance in order to attract investors. With the increase in profits, it is expected that the dividends distributed to investors will also increase, thus attracting other investors who have not invested their capital to look at the company's shares. Ultimately, the demand for shares from this company will increase, which of course will have an impact on increasing the company's share price and increasing the company's value as well. Company value is closely related to stock prices, when the company's share price increases, the company's value will also increase, and vice versa. This study aims to analyze the effect of information asymmetry, corporate social responsibility, and intellectual capital on company value. The objects of the study are companies listed on the LQ45 index on the Indonesia Stock Exchange. Data analysis uses multiple regression analysis. The results of the study indicate that information asymmetry has a negative effect on company value, while corporate social responsibility and intellectual capital do not affect company value.